Revisiting the Thermal Transitions of Polydimethylsiloxane (PDMS) Elastomers: Addressing Common Misconceptions with Comprehensive Data - Saul Utrera‐Barrios; Liyun Yu; Anne Ladegaard Skov (Macromolecular Materials and Engineering)
Abstract An important characteristic of silicone elastomers is their ability to maintain their properties over a wide temperature range. This results from the Si─O bond's high flexibility and thermal stability, causing a very low glass transition temperature (Tg) and a high degradation temperature (Td), respectively. However, other thermal transitions, such as crystallization (Tc), cold crystallization (Tcc), and melting (Tm), must also be considered to ensure the elastomers’ optimal performance and use. This study addresses the misconceptions surrounding the assignment of these transition temperatures for the most prevalent type of silicone elastomer, namely polydimethylsiloxane (PDMS) elastomers. The article focuses on rectifying these misunderstandings, particularly in the context of high‐tech applications, including aerospace, automotive, coatings, and soft robotics. A diverse range of 15 types of silicones are meticulously analyzed, including elastomers, adhesives, and oils, using differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), and thermogravimetric analysis (TGA). This study highlights these transition temperatures’ role in shaping silicone elastomers’ thermomechanical behavior and their significance for effective utilization in advanced applications.